2015
DOI: 10.1038/ncomms7128
|View full text |Cite
|
Sign up to set email alerts
|

Seeded growth of highly crystalline molybdenum disulphide monolayers at controlled locations

Abstract: Monolayer transition metal dichalcogenides are materials with an atomic structure complementary to graphene but diverse properties, including direct energy bandgaps, which makes them intriguing candidates for optoelectronic devices. Various approaches have been demonstrated for the growth of molybdenum disulphide (MoS 2 ) on insulating substrates, but to date, growth of isolated crystalline flakes has been demonstrated at random locations only. Here we use patterned seeds of molybdenum source material to grow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
233
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(249 citation statements)
references
References 33 publications
10
233
1
1
Order By: Relevance
“…The recent studies of growth concerning various 2D materials [14][15][16][17] has opened the possibility to design van der Waals (vdW) heterostructures using graphene as an underlayer, which provides more opportunities for achieving desired electronic or optoelectronic properties 3,[18][19][20][21][22][23][24] . In fact even if graphene has exceptionally high mobility at room temperature, for optoelectronics 9 the overall low absorption of a single carbon layer (≈ 2%) and the absence of band gap implies that graphene needs to be combined with some semiconductor compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies of growth concerning various 2D materials [14][15][16][17] has opened the possibility to design van der Waals (vdW) heterostructures using graphene as an underlayer, which provides more opportunities for achieving desired electronic or optoelectronic properties 3,[18][19][20][21][22][23][24] . In fact even if graphene has exceptionally high mobility at room temperature, for optoelectronics 9 the overall low absorption of a single carbon layer (≈ 2%) and the absence of band gap implies that graphene needs to be combined with some semiconductor compounds.…”
Section: Introductionmentioning
confidence: 99%
“…12,18 In a typical transfer process, the original substrate with MoS 2 crystals is spun coated (4000 rpm/45 s) with PMMA and then immersed in a KOH (0.1M) solution. The SiO 2 layer is slowly dissolved by KOH and the PMMA film with the MoS 2 is washed with water and transferred on to the split gate FET substrate and dried.…”
Section: Methodsmentioning
confidence: 99%
“…The charge mobility in these materials exceed 200 cm 2 /V-s for exfoliated MoS 2 13-15 and ∼ 10 cm 2 /V-s for CVD grown MoS 2 on SiO 2 substrates. 8,10,12 Being a stable n-type semiconductor, MoS 2 has potentially wide range of applications in the fields of nanoelectronics (FET, diodes) and energy harvesting (photovoltaics, solar cells). An important electronic device for practical applications is a FET, since it forms the basic building block in logic circuits and switches for displays and is thus widely studied using organic and inorganic semiconducting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although wafer-scale uniformity could be achieved in various synthesis methods as discussed above, the growth of high-quality large-area single crystal thin film is still the main challenge for further nanoelectronic applications of TMDCs. Han et al reported an alternative approach, in which the deposition of a seed layer enables selective growth of single crystalline TMDCs at controlled spatial locations (shown in Figure 3o) [71]. This provides more insight on the growth mechanism of TMDCs and the potential solution towards high-quality large-area TMDC thin film growth for optoelectronic applications.…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%